1997
DOI: 10.2134/agronj1997.00021962008900050019x
|View full text |Cite
|
Sign up to set email alerts
|

Symbiosis with Neotyphodium uncinatum Endophyte May Increase the Competitive Ability of Meadow Fescue

Abstract: Infection with the endophyte Neotyphodium uncinatum (Gams, Petrini & Schmidt) Glenn, Bacon, Price & Hanlin may influence drought resistance and competitive ability of meadow fescue (Festuca pratensis Huds.). We determined endophyte‐related effects on some growth and physiological characteristics in one clone of meadow fescue. In a growth chamber experiment, meadow fescue and orchardgrass (Dactylis glomerata L.) were planted in pots as monocultures or binary mixtures, competing in the root systems. One group of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
51
0
1

Year Published

1999
1999
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(56 citation statements)
references
References 27 publications
4
51
0
1
Order By: Relevance
“…did not change root/shoot ratios. In other work with meadow fescue, Malinowski et al (1997b) reported greater growth response in roots of endophyte-infected plants, than in the shoots, but did not present root/ shoot ratios. Lewis et al (1996) working with clonal ryegrass in solution culture found that endophyte infection decreased root/shoot ratios in both high and low N supply treatments, but the effect was transitory in the low N solution.…”
Section: Introductionmentioning
confidence: 68%
“…did not change root/shoot ratios. In other work with meadow fescue, Malinowski et al (1997b) reported greater growth response in roots of endophyte-infected plants, than in the shoots, but did not present root/ shoot ratios. Lewis et al (1996) working with clonal ryegrass in solution culture found that endophyte infection decreased root/shoot ratios in both high and low N supply treatments, but the effect was transitory in the low N solution.…”
Section: Introductionmentioning
confidence: 68%
“…This phenomenon is particularly well documented in the agricultural grasses Festuca arundinacea and Lolium perenne infected by Neotyphodium endophytes where these metabolites cause toxicosis in cattle and sheep (Rowan, 1993 ;Bacon, 1995). Infected plants also often show enhanced growth and increased competitive abilities (Clay et al, 1993 ;Malinowski et al, 1997), as well as increased resistance to drought, pests and\or pathogens (Kimmons et al, 1990 ;Gwinn & Gavin, 1992 ;West, 1994 ;Schuster et al, 1995 ;Elbersen & West, 1996).…”
Section: mentioning
confidence: 99%
“…Endophytes of Neotyphodium species and their sexual telemorphic genus Epichloë have been found in many cool-season grasses [4,5] and are associated with increased host resistance to abiotic and biotic stresses [6][7][8], nutrient acquisition [9] and competitive ability [10,11].…”
Section: Introductionmentioning
confidence: 99%